What is it “about us”? Using AntConc and ChatGPT to analyse the discourse of websites of language and linguistics conferences - Daron Benjamin Loo (Pusat Penataran Ilmu dan Bahasa,Universiti Malaysia Sabah, 2024)
Conferences in the areas of language and linguistics have proliferated globally. These academic events offer more than just the opportunity to share research work or to engage with the community of practice; they have also been commodified through the feature of publication possibilities. This has resulted in conferences being in competition with one another. To maintain distinctness or to stand out, conferences would need to be strategic in their discursive portrayal. In this presentation, observations would be drawn on the discourse from language and linguistic conferences. Specifically, texts that explain what the conference is about (or the “about us” page or paragraph) will be examined. Two discourse analysis tools were used, namely AntConc 3.5.9 (Macintosh OS X) 2020 and ChatGPT 3.5. Discourse data was collected from language and linguistic conferences listed on Conal Conference Alerts. Only conferences with the words “language” and “linguistic”, and taking place in 2024 were included. A total of 19 conferences were identified; however, only 15 conferences had texts related to “about us”. The texts were analysed for keywords. Results from AntConc featured words from the actual discourse data, most of which may not be surprising considering their discourse context; nonetheless, one interesting keyword that emerged was “interdisciplinary”. Results from ChatGPT, on the other hand, interpreted meaning from the discourse data. Salient keywords identified by ChatGPT were “cross-disciplinary”, “international conference”, and “global forum”. Based on this preliminary analysis, one main observation drawn about language and linguistic conferences is its focus on the notions of interdisciplinary and crossdisciplinary. In terms of discourse analysis tools, using AntConc would still require close engagement between researcher and data, while using ChatGPT may offer an interpretation of the data. The latter may pose challenges, especially if researchers are expected to identify linguistic evidence for its analytical interpretation.